2021
DOI: 10.1097/ans.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Accuracy of Cited References in a Selected Data Set of Nursing Journal Articles

Abstract: Accuracy of cited references in scholarly publications gives credit to original authors and offers information for readers to access sources for additional review. Errors in this foundational information can, at a minimum, create confusion and additional burden for consumers; at worst, these errors can make it impossible to locate the original work. For systematic and other types of reviews, finding relevant studies is critical for comprehensiveness and accuracy. The purpose of this study was to evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Only 19% of errors were likely to cause problems in retrieving articles. Most recently, Nicoll et al 4 found that in their review of 666 references from 100 articles, errors prevented only 1.3% from being retrieved. They attribute this finding to the increased use of DOIs (digital object identifiers) and reference management software, which reduced author transcription errors by automatically importing and formatting references.…”
Section: Citation Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 19% of errors were likely to cause problems in retrieving articles. Most recently, Nicoll et al 4 found that in their review of 666 references from 100 articles, errors prevented only 1.3% from being retrieved. They attribute this finding to the increased use of DOIs (digital object identifiers) and reference management software, which reduced author transcription errors by automatically importing and formatting references.…”
Section: Citation Errorsmentioning
confidence: 99%
“…Only 19% of errors were likely to cause problems in retrieving articles. Most recently, Nicoll et al 4 . found that in their review of 666 references from 100 articles, errors prevented only 1.3% from being retrieved.…”
Section: Commonly Encountered Inaccuraciesmentioning
confidence: 99%